Riscos e estratégias de prevenção na triagem de materiais recicláveis - Jussara Cardoso Rajão (2018)
Waste picking is present in large cities of Brazil and has long been part of the expression of resistance and struggle for survival of an excluded population living in informality. Nevertheless, part of this population of workers increasingly seeks their rights and recognition in the political and economic scenario of the country by organizing associations and cooperatives. In these waste picking cooperatives, they find work situations more favorable than on the streets, in dumps or in landfills. But still, they faced unhealthy and precarious conditions. In addition, these conditions offer varying health hazards related to biological, chemical, physical and ergonomic risks. Thus, the objective of this master’s thesis is to understand the role of risk perception and mitigation strategies developed by the workers and stimulate the sharing of these practices in order to reduce damages to health. For the accomplishment of the research I have used qualitative methods including Ergonomic Analysis of the Work, Grounded Theory and participant observations. This approach of data collection and analysis has allowed me to understand the activity of the workers of a cooperative of recyclable materials, as they seek to avoid or minimize injuries and health problems. The research reveals contrasting visions between workers and the researcher regarding health, risks, strategies and the economy of the body. This suggests that the development of strategies that promote the economy of body and preserve heath should emerge from waste picker’s practices.